THE EFFECT OF BABY MASSAGE ON INCREASING BODY WEIGHT IN INFANTS AGED 2-5 MONTHS AT GRIYA SEHAT INDONESIA - Francisco Septiana; Dwi Lukmawati; Angelina Van Costa Fernandes; Neta Ayu Andera (Kirana Publisher, 2023)
Baby massage is tactile stimulation and has become an ancient tradition that has been studied through research on neonatal sciences, neurologists, child psychology, and several health sciences. Massage or touch on the baby provides benefits that make the baby feel calm, improve the quality of baby's sleep, teach the baby early about body parts and stimulate the baby's appetite. This study aims to determine the effect of giving baby massage on increasing body weight in infants aged 2-5 months in Griya Sehat Indonesia. The method used is Pre experimental with a one group pretest posttest design. The population in this study was all infants aged 2-5 months in Griya Sehat Indonesia, a total of 35 babies taken by purposive sampling technique. The data analysis used in this study was the Wilcoxon Test. Results: Before the baby massage, most of the respondents gained weight, which was as many as 15 respondents (57.7%). After baby massage, almost all of the respondents gained weight, namely as many as 23 respondents (88.4%). And a small percentage of respondents did not gain weight, which was as many as 3 respondents (11.6%). Conclusion: There is an effect of giving baby massage on the weight gain of babies aged 2-5 months in Di Griya Sehat Indonesia